Effects of intradialytic parenteral essential amino acid suplementation in hemodialysis patients (Annals of Medical Research, 2021)
None
Keywords: s : Hemodialysis, essential amino acid supplementation, chronic renal failure, malnutrition, protein catabolic rate.